Development of a participatory action research approach for four agricultural carbon projects in East Africa - Shames, Seth; Bernier, Quinn; Masiga, Moses (International Food Policy Research Institute, 2013)
This paper describes an action research process undertaken with four African agricultural carbon projects—CARE’s Sustainable Agriculture in Changing Climate Initiative in Western Kenya; World Vision’s Assisted Natural Regeneration Project in Humbo, Ethiopia; Vi Agroforestry’s Western Kenya Agricultural Carbon Project; and ECOTRUST’s Trees for Global Benefits in Uganda—to explore their institutional changes as project managers and communities work to build local capacity for project management. It describes the research protocol as well as the process by which it was collaboratively developed by researchers and carbon project managers. The paper also reports the results of the field work in each of the projects, which will be used to identify actions that they will implement in the next step of the action research process. The tools were generally successful in gathering the desired data, although modifications could allow future efforts to target questions to interviewees more effectively, include additional stakeholder groups such as government agents and project service providers, develop capacity for local-level data collection and analysis, and focus additional attention on local-level innovations and landscape-level coordination. The research yielded diverse topics for action across projects, as the projects are structured differently and are at different stages of development. Common themes included the need for partnership development, enhanced training of trainer programs, improvements in the sense of community ownership of projects, and stronger foundations for collective action throughout project and community institutions.